2015
DOI: 10.1364/ol.40.002572
|View full text |Cite
|
Sign up to set email alerts
|

Slow-light all-optical soliton diode based on tailored Bragg-grating structure

Abstract: An all optical soliton diode (AOSD) is proposed based on a sandwich nonlinear Bragg-grating structure: a linearly chirped Bragg-grating linked to a uniform Bragg-grating and again to a chirped Bragg-grating. The nonreciprocity is achieved by introducing two spatially asymmetric chirped Bragg-gratings with optical nonlinearity. High transmission ratio up to 150 is obtained when launching a picosecond Gaussian pulse into the setting. We find that such pulses in a form of solitons propagate at a rather small velo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
(42 reference statements)
0
13
0
Order By: Relevance
“…BG solitons in dual core systems can be a potential candidate for various novel optical devices (e.g., all-optical soliton diode reported in ref. 62). …”
Section: Introductionmentioning
confidence: 99%
“…BG solitons in dual core systems can be a potential candidate for various novel optical devices (e.g., all-optical soliton diode reported in ref. 62). …”
Section: Introductionmentioning
confidence: 99%
“…We should mention that the proposed scheme is different from that reported in the sandwich FBG structure [17] and the photonic bandgap liquid-crystal heterojunctions [31]. We note that the chirped CLCs, which is equivalent to the chirped Bragggratings (CBGs) in FBG [32], can be practically achieved by the experiment [33].…”
mentioning
confidence: 86%
“…This phenomenon has been explained in Ref. [17]: the propagation dynamics of solitons can be approximately considered as a quasi-particle propagating in the setting, which cannot exhibit unidirectional transmission in an effective potential. However, a Gaussian optical pulse that is not an exact solution of the soliton and cannot use the quasi-particle approximation during the time when the pulse is developing into a soliton.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16 However, majority of these works neglect the shape of the optical field, which plays a critical role in optical light processing with information after propagating through the devices. Recently, it is reported that soliton-diode in the temporal and spatial domains is realized on the tailored Bragg grating structure 17,18 and discrete waveguide array, 19,20 respectively.…”
Section: Introductionmentioning
confidence: 99%